Reabilitação psicossocial no CERSAM: uma história de "vida" - Julia Coutinho Nunes Castilho (2013)
With the beginning of the Brazilian Psychiatric Reform movement in the late 70s, the view on the craziness and the model of care and attention began to change. With the emergence of new health services in replace to hospitals such as the Centers of Mental Health Reference (CERSAMs - CAPS III) in Belo Horizonte, the proposal is now to accompany users in crisis in their own context, without breaking their daily relationships. This research aims to contribute to the practice of psychosocial rehabilitation care and mental health by combining theoretical reflections to empirical practice, consolidating experience and bringing the Universitys knowledge closer to clinical practice. This is a work of dialogue, creating interfaces between the University and the staff of the mental health service. This dissertation will specifically search to understand the psychosocial rehabilitation process in CERSAM (CAPS III) through the concepts and theories of everyday personal care, affected as an instrument of social construction and citizenship, analyzing a severe case considered successful from the standpoint of the staff that dealt with it. It searches to understand the complexity of the process, opening reflections on psychosocial rehabilitation and everyday life of users and mental health services. The research objectives are to investigate how the process of psychosocial rehabilitation offered by CERSAM transforms the everyday life of the psychiatric patient in psychiatric crises, to systematically qualify how the treatment offered in CERSAM brings benefits to people with mental illness and to the service itself. In regard to the challenges of the first objective, it is necessary to reflect about the routine that supports rehabilitative practice, to analyze the theoretical contributions of the practice of psychosocial rehabilitation process in dialogue with the reality of substitutive services of the health network of Belo Horizonte, and finally to reflect about the course of the treatment of a user of CERSAM. In order to reach them, we opted to conduct a qualitative research, as well as to do a case study of a user of CERSAM, using the life story method. In the exploratory phase we used the concepts and ideas around psychosocial rehabilitation and everyday life. The fieldwork combined the tools of observation, communication and data collection. Studying and discussing this case means producing anti-maniacal culture. The rehabilitation project must be done with the user who needs it, case by case, facing their risks and concrete possibilities. The interviewee was able to recover in public life some of their basic rights of citizenship, and in private life, the tenuous possibility of dialogue and choice. In conclusion, the case illustrates the assertion that CERSAM is not only a place to deal with the crisis, but also to host serious and complex cases. It also concludes that we can organize the various concepts around rehabilitation into at two lines of thought: the adaptationist one, and the politicized one. We can integrate some of these concepts and reach a wider understanding of psychosocial rehabilitation.